Online reading comprehension: challenges and opportunities - Coiro, Julie (Texto Livre, 2014)
ABSTRACT: This paper details a number of challenges and opportunities for today’s learners when reading for information on the Internet. After defining online reading comprehension from a new literacies perspective and how it appears to be different than offline reading comprehension, I highlight details about four of the biggest challenges for today’s learners. These include 1) understanding and becoming proficient with the new literacy skills and practices needed for online research; 2) developing a special kind of digital wisdom that focuses on learning how to learn with the Internet; 3) taking on new roles in a digital culture that expects learners to actively participate and contribute with new knowledge as a member of their community; and 4) developing positive attitudes toward using the Internet for academic work. The second part of the paper shares examples of how skilled online readers can use the steps of online inquiry to think more deeply about topics that interest them; develop a personal voice as they share ideas with others; and work collaboratively to build meaning and new digital products that enable them to make a difference in their world, or matter. You can explore the research and resources from this presentation in more depth at <http://coiroevidosol.wikispaces.com/>. KEYWORDS: online reading comprehension; online inquiry; digital literacy; reading on the Internet; online readers. RESUMO:Este artigo detalha alguns desafios e oportunidades para o aprendiz contemporâneo, quando ele lê para obter informações na Internet. Depois de definir a compreensão da leitura online pela perspectiva dos novos letramentos e de mostrar como ela parece se diferir da leitura do impresso, eu destaco detalhes a respeito de quatro dos maiores desafios para os aprendizes na atualidade. Eles incluem: 1) compreender e se tornar proficiente nas habilidades dos novos letramentos e nas práticas necessárias para a pesquisa na Internet; 2) desenvolver um tipo especial de conhecimento digital que focaliza o aprender a aprender com a Internet; 3) a assumir novos papéis na cultura digital que espera que alunos, como membros de uma comunidade, participem ativamente e contribuam com ela trazendo novos conhecimentos; e 4) o desenvolvimento de atitudes positivas em relação ao uso da Internet para o trabalho acadêmico. Na segunda parte do artigo compartilho exemplos de como leitores de Internet habilidosos podem usar as etapas da pesquisa online para pensar mais profundamente sobre temas que interessam a eles; como podem desenvolver sua própria voz quando eles trocam idéias com outras pessoas; e de como eles podem trabalhar de forma colaborativa para construir sentidos e produtos digitais que lhes permitam fazer a diferença em seu mundo, ou naquele assunto. Você pode explorar a pesquisa e os recursos usados nesta apresentação de forma mais aprofundada no <http://coiroevidosol.wikispaces.com/>. PALAVRAS-CHAVE: compreensão da leitura on-line; pesquisa on-line; letramento digital; leitura na Internet; leitores online.